Evaluation Of Antibacterial Potential Of Thiazole,Sulfonamide And Indole Derivatives Against Fima Of P.Gingivalis Using In Silico Molecular Docking And Admet Prediction - Sree Lakshmi; Parkavi Arumugam; Rajalakshmanan Eswaramoorthy (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Aim : The main aim of the study is to evaluate the antimicrobial potential of thiazole, sulfonamide and indole derivatives against FimA of P.gingivalis using molecular docking techniques. Introduction: Periodontal disease is a chronic inflammatory disease of the supporting structure of the teeth that causes gum inflammation, periodontal tissue degeneration, almost complete loss of alveolar bone, and eventually tooth exfoliation. The numerous interactions between P. gingivalis and the host immune system, together with its numerous virulence factors, such as fimbriae, cysteine proteinases, hemagglutinins, and lipopolysaccharide (LPS), clearly indicate its potency as a pathogen. Materials and method : Utilizing ChemDraw and Chem3D software, the 2D structures (mol) of the thiazole, sulphonamide, and indole compounds (NN1-NN9) were created. The selected molecules were handled quantum mechanically by applying the DFT approach using the Gaussian 09 programme suite at the Becke3-Lee-YangPar (B3LYP) level and the common 6-31G (d,p) basis set. In order to create a stable construction with the least amount of energy, all of the parameters were chosen during the optimization process.Results and discussion : Red complex bacteria have a significant role in the aetiology of periodontitis, which is an illness with several factors. The more dangerous red complex bacteria are the last bacteria to colonize and cause the breakdown of the periodontium. So based on ADMET prediction compound 4 (NN4) can be used as a potential drug for further investigations by eliminating the hepatotoxicity alone.Conclusion : In this study, molecular docking was used to determine that NN4 had superior properties to already approved clinical drugs in terms of inhibiting the activity of P. gingivalis and acting as an adjunct or substitute for antibiotics in the treatment of periodontitis.